The U.S. Civil War why they fought - Grayson, Robert (North Mankato, Minnesota Compass Point Books, a Capstone imprint, 2016)
Examines reasons why the major combatants fought in the U.S. Civil War and how those motivations changed throughout the war
A gift from book Afica
History
1 2 13 15
Keywords: United States -- History -- Civil War, 1861-1865 -- Juvenile literature; United States -- History -- Civil War, 1861-1865 -- Causes -- Juvenile literature